An Analysis of Factors Influencing Crude Oil Prices - Čech, Petr (2013)
This master thesis is focused on the investigation of drivers within crude oil markets. The main goal is to analyze the influence of various factors on the crude oil price. In the theoretical part, the theoretical background and also academic studies which examine the relationship between diverse fundamental variables and crude oil price are presented. In the analytical section, I attempt to take a different approach to other authors when investigating some relevant factors and actually examine different factors than are usually researched. Where appropriate, I run cross-sectional regressions to examine whether relative changes in the oil price can be explained by relative changes of a particular factor. Also, I construct two complex models which are able to explain about 60% of crude oil price variation.